Confucius, Wisdom, and Political Participation: Benevolence and Timeliness in the Analects. Issue 2 (3rd January 2023) - Morrow, Sydney; Ryan, Shane
Abstract: This paper aims to address when the wise person should participate in politics. The question is addressed through engagement with the Analects. Rather than provide interpretations of key terms in the Analects, we provide an account of wisdom that draws from themes in the Analects . The case is made that the wise person is committed to participating in politics primarily because of the connection between wisdom and benevolence ( ren 仁 in the Analects ). We address challenges to the Confucian approach from the Zhuangzi concerning the potential harms of political participation. General political disengagement is not considered exemplary on the Confucian approach to wisdom, although when political engagement may be eschewed is explored. Finally, the case is made that while ren motivates the wise to participate politically, the wise also have a sense of timeliness that provides guidance as to when to refrain or withdraw from political participation.